Correction: Who Lives Where and Does It Matter? Changes in the Health Profiles of Older People Living in Long Term Care and the Community over Two Decades in a High Income Country. - Cognitive Function and Ageing Studies (DFAS) (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0161705.].